2000
DOI: 10.1161/01.hyp.35.4.1002
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Intraluminal Pressure Inhibits Vascular Tissue Plasminogen Activator Secretion and Downregulates Its Gene Expression

Abstract: Abstract-We recently discovered that patients with essential hypertension have a markedly impaired capacity for stimulated release of tissue plasminogen activator (tPA) from vascular endothelium. This defect may reduce the chance of timely spontaneous thrombolysis in case of an atherothrombotic event. We now investigated whether increased intraluminal pressure as such may depress vascular tPA release or downregulate its gene expression. Segments of human umbilical veins were studied in a new computerized vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…We recently demonstrated in an ex vivo perfusion model that both tPA synthesis and release from endothelial cells in isolated human conduit vessels was markedly suppressed when intraluminal pressure was elevated to the high physiological range. 4 The intracellular signal transduction pathways mediating the effect of intravascular pressure are, as yet, not fully elucidated, but this observation offers a potential explanation for the observed defective tPA secretory response in patients with high blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated in an ex vivo perfusion model that both tPA synthesis and release from endothelial cells in isolated human conduit vessels was markedly suppressed when intraluminal pressure was elevated to the high physiological range. 4 The intracellular signal transduction pathways mediating the effect of intravascular pressure are, as yet, not fully elucidated, but this observation offers a potential explanation for the observed defective tPA secretory response in patients with high blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that the capacity for tPA release is markedly impaired in patients with untreated primary hypertension, 3 and further experimental ex vivo studies indicated that this defect could be because of the elevated intraluminal pressure per se. 4 Chronic kidney disease (CKD) is frequently accompanied by hypertension and also with a markedly increased risk of atherothrombotic complications. 5 The association of CKD with thrombotic events is somewhat puzzling because renal disease is typically associated with increased bleeding tendency due to platelet dysfunction and disturbed plasma coagulation.…”
mentioning
confidence: 99%
“…Serum from smokers, but not from nonsmokers, reduced substance P-induced t-PA release from cultured endothelial cells, 96 suggesting that a blood-borne mediator may affect endothelial t-PA responses. Using ex vivo human umbilical veins, increased intraluminal pressure decreased t-PA release as well as gene and protein expression, 97 suggesting that raised intraluminal pressure might itself impair t-PA release. Detailed characterization of the path-ways of t-PA secretion and how these are affected by different stimuli will provide a platform for the investigation of the mechanisms of impaired secretion.…”
Section: Future Workmentioning
confidence: 98%
“…28 Elevated intraluminal pressure can also lead to downregulation of tissue plasminogen activator, a promoter of fibrinolysis/thrombolysis, which is impaired in patients with hypertension. 29 Angiotensin II also increases production of plasminogen activator inhibitor-1, which is both a major inhibitor of fibrinolysis and is antiproteolytic, thus promoting matrix accumulation. 30 Aldosterone independently contributes to renal injury, as well.…”
Section: Pathophysiologymentioning
confidence: 99%